THE INVOLVEMENT OF COMMUNITY IN MANAGEMENT OF TABUIK TOURISM EVENT PARIAMAN CITY WEST SUMATERA PROVINCE - Reni Nurul Husnah; Siti Sofro Sidiq (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Tabuik is a cultural heritage in the form of ritual or ceremony that developed in Parimansince about two centuries ago. This event was held to commemorate the death of Husain(grandson of the Prophet Muhammad) in battle in Karbala and it’s done every 1-10 / 14Muharram by involving stakeholders. The community re-presented some fragmentsaccording to the Pariaman community's interpretation in the form of 7 rituals or ceremonies.The purpose of this research to determine community involvement in management of TabuikTourism Event Pariaman City West Sumatera Province. This research used eventmanagement as the concept. This research is qualitatif research with descriptive. Methodand data sources obtained withinterview, documentation, and literature study, determinationtechnique using purposive informant sampling is subjective determination. Based thisresearch, there is community involvement in management of Tabuik tourism event start fromplanning, involved in organizational structure. Involvement in the implementation especiallyfor every ritual and various products produced by the community. And communityinvolvement in the evaluation of each activity. Factors that influence community involvementin management are internal (ownership, community identity, and solidarity) and external(roles in organization, knowledge and education, economics) factors.Keywords: tourist attraction, event management, community-based tourism